Randomised controlled trials in child health in developing countries: trends and lessons over 11 years. Issue 7 (10th March 2014) - Duke, Trevor; Fuller, David
Abstract : Using a uniform systematic approach annually, we reviewed 1553 publications from randomised controlled trials in child health in developing countries published between July 2002 and June 2013. There were annual increases in such publications, from 38 in the 12 months to July 2003 to over 200 in each of 2012 and 2013. These trials involved children in 76 developing countries. Studies of nutrition (366 publications, 23.6%) and malaria (336 publications, 21%) predominated. 79% of nutrition trials have been of micronutrients (288 publications), with comparatively few publications related to macronutrient interventions or complimentary feeding (48 publications) or measures to improve breast feeding (20 publications). Trials of malaria have involved a comprehensive range of treatment and preventive strategies and have heralded the implementation of new interventions as routine health strategies, and reductions in malaria in each affected country in the world in the last decade. There have been a relatively small number of trials of interventions for treatment or prevention of acute respiratory infection (98 publications, 6.3%), neonatal health (64 publications, 4.1%) and tuberculosis in children (26 publications, 1.7%). In the last 5 years there has been increasing focus on non-communicable diseases such as asthma and allergy, obesity, diabetes and cardiac disease, and behavioural-developmental disorders. Mental health conditions have received little attention (21 publications, 1.4% of publications). There is increasing research activity and capacity in child health in developing countries. Some areas have been the subject of a large amount of research, and have led to the design and implementation of effective public health interventions and reduced disease burdens, while in other areas comprehensive approaches and the systematic application of research findings have been lacking.